Implementasi Pemupukan Kelapa Sawit (Elaeis guineensis jacq) Pola Masyarakat Pada Lahan Pasang Surut di Desa Bangko Kanan dan Bangko Kiri Kecamatan Bangko Pusako Kabupaten Rokan Hilir - Nurlela '; Armaini '; Gulat ME Manurung (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
One alternative land for oil palm cultivation is tidal land, but many abstacles tidal land for the cultivation of plan on agronomic, pattern of wichh the water system and the limitations of physical and chemical condtions, aluminium, low fertility and salinity toxicity. To overcome these problems is necessary for an appropriate processing technologie and efficient, one of them is with the proper fertilizer. Purpose of this study is to investigate the implementation of palm fertilizer made by the comunity on tidal land in the district of Rokan Hilir Bangko Pusako. This research was conducted in tidal land and village right Bangko and Bangko districts left Pusako Rokan Hilir. This study uses survey method and technique of determining the population as on object of study usingPurposiveRandom Samplingmethod. Sample size of at least 5% of the total population that is determined proportionally, the data implementation fertilization and cultivation techniques were analyzed kualitatif and are tabulated in table form. Seen from fertilization concept that farmers have not been doing fertilizing with right timing with presentation as 87,5%, the recommended dose 100%, type of fertilizer I needed plant5%,how fertilization100% and quality manner fertilizer 5%, growth resulting oil palm farmers growth sample is not optimal, as yellowing leaves, young leaves, young leaves or shoots broken, drid up old leaves, leaf curl or wrinkle, rods, small hump and draw plant and were cultivated by the optimal growth of plantation service like leaf green, fully, developed leaves, bigger trunk, large tubers and plant are not stunted. Keyword: Palm oil plant, tidal land, implementasi of fertilizer.